Impacto de um programa STEWARDSHIP de antimicrobianos implementado em um Hospital Universitário - Mendonça, Simonize Cunha Barreto de (2022)
The rational use of antimicrobials is a challenge for global health services. One strategy used to control the spread of multidrug-resistant bacteria is antimicrobial management programs. This is a pre- and post-intervention study that assesses the impact of an antimicrobial stewardship program in a hospital through evaluating clinical and microbiological outcomes, usage measures and costs. The sample was randomly stratified and proportionally distributed across the inpatient units each month, and comprised adult patients hospitalized for more than 24 hours during the period from August 2017 to March 2018 (pre-intervention), and August 2018 to June 2019 (post-intervention). Primary outcomes included length of therapy (LOT), days of therapy (DOT) and defined daily dose (DDD) per 1000 patient-days (pd), the DOT/LOT ratio, the incidence of oxacillin-resistant Staphylococcus aureus and coagulase- negative Staphylococci, carbapenem-resistant gram-negative bacteria and extended-spectrum beta-lactamases producers, and the costs of therapy. Secondary outcomes were the use of antimicrobials and antimicrobial prescriptions by class, hospital length of stay rates, and mortality rates. Data were obtained from medical prescriptions, pre-authorization forms for restricted antibiotics, and microbiological tests, and analyzed using Stata software version 15.1, comparing non-critical and critical care units, with a significance level of 0.05. A total of 2,704 patients were evaluated and there was a significant post-intervention reduction of exposure to antimicrobials of 8.1% and of 90 days in respect of the LOT in non-critical units. The greatest variations in DOT were with antifungals and carbapenems in non-critical units, and lincosamides, 4th generation cephalosporins and glycopeptides in critical units. There were significant reductions in the DDD of ampicillin+subactam, ciprofloxacin and fluconazole in the non-critical units. There was a reduction of more than 50% in the costs of therapy and of 1.2 days in the length of hospital stay in non-critical units. There was no variation in bacterial resistance. Although the stewardship program and its interventions reduced antimicrobial consumption, costs and the length of hospital stay, however, the impact on microbiological outcomes requires further studies with a multicenter profile and larger sample size.